The Impact Of Community Based Tourism On Community Development In Sarawak - Parveen, Kaur; Arif, Jawaid; Norizan, Bt Abu Othman (Institute of Borneo Studies, UNIMAS, 2016)
Community Based Tourism (CBT) or homestay is a new form of tourism product in which tourism is managed by the local communities. The local communities are fully responsible in every aspect of their tourism management ranging from decision making, planning and evaluation. The main approach of CBT is to empower the local communities while emphasizing environmental, social and cultural sustainability. Moreover, CBT provides tourists with the learning process about the community lifestyle, local culture and customs. It gives the tourists interaction opportunity with local communities on the cultural heritage and natural environment. CBT is lifeblood for the sustainability of homestay industry in Malaysia. Apart from improving the life standard of local communities, the main agenda of the CBT is to preserve the socio-cultural status and the environment of the local communities.This study examines the factors affecting the sustainable management of CBT. It covers 20 homestays in three villages in Sarawak. They are Kampung Annah Rais, Padawan, Kampung Tebekang Melayu, Serian and Kampung Santubong, Kuching. This study concludes that CBT has a significant impact on the community development.